2001
DOI: 10.1002/jmv.1079
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus involvement is mainly restricted to lymphoepithelial type of gastric carcinoma among various epithelial neoplasms

Abstract: To demonstrate the association of Epstein-Barr virus (EBV) with primary epithelial neoplasms in the south part of Kyushu, Japan, 761 carcinomas consisting of 75 lung, 61 breast, 107 esophagus, 102 colon, 58 pancreas, 45 thyroid, and 313 gastric cancers were examined by EBER-1 in situ hybridization. EBER-1 was detected in 23 cases (7.3%) out of 313 gastric carcinomas, while none of the other carcinomas was positive for EBER-1. Twenty-eight (9.4%) out of 313 gastric carcinomas were differentiated poorly to moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
4
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 26 publications
1
59
4
2
Order By: Relevance
“…In our study, 1 case of adenoma complicated with dysplasia showed positive signals for EBER. This finding was different from the observation of Kijima et al, Yuen et al and Cho et al [21,22,24] . Moreover, detection of EBV in 1 case of dysplastic adenoma suggested that EBV infection occurred in the dysplastic phase before the occurrence of colorectal carcinoma, further indicating that EBV may play a role in tumor progression.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…In our study, 1 case of adenoma complicated with dysplasia showed positive signals for EBER. This finding was different from the observation of Kijima et al, Yuen et al and Cho et al [21,22,24] . Moreover, detection of EBV in 1 case of dysplastic adenoma suggested that EBV infection occurred in the dysplastic phase before the occurrence of colorectal carcinoma, further indicating that EBV may play a role in tumor progression.…”
Section: Discussioncontrasting
confidence: 90%
“…Yuen et al [22] investigated for the presence of EBV in 74 cases of gastric adenocarcinoma and 36 cases of colorectal adenocarcinoma from Chinese patients by in situ hybridization (ISH) using an antisense EBER probe, but none of the colorectal carcinomas showed a positive signal. Kijima et al [21] demonstrated the association of Epstein-Barr virus (EBV) with primary epithelial neoplasm in the south part of Kyushu, Japan, they found that there were no positive signals in 102 cases of colorectal cancer using EBER in situ hybridization. Cho et al [24] reported the same result that EBV was not associated with colorectal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, significant differences are observed in terms of cell differentiation and viral gene expression in epithelial malignancies associated with EBV [8]. In addition, it appears that the relationship between EBV and certain epithelial neoplasia depends on the patients' regional or ethnic backgrounds [7,25]. Perhaps one reason for the lower prevalence of EBV in patients with CRC compared to patients with gastric carcinoma is the preferential residence of EBV in the upper gastrointestinal tract and lympho-hematopoietic tissues compared to the colorectal region [26].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of a significant association between EBV detection and the incidence of cancer, relevant research has demonstrated the contribution of this virus to the progression of adenocarcinoma and carcinogenesis [25,31,33,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The infection rate of EBV was significantly higher in HCC patients than in control patients. [20][21][22][23] , esophageal cancer [24,25] , gastric cancer and colorectal cancer. It has been reported that the correlation between EBV and tumor incidence is stronger in Japan and Taiwan than in the western countries.…”
Section: Discussionmentioning
confidence: 99%